The impact of budget deficits on GDP in EU countries from 2000 to 2022 - Šare, Dalibor; Tošev, Dejan (Poslovna ekonomija, 2025)
The budget deficit is a topic that has a significant impact on economic development and stability. It occurs when government spending exceeds revenues, which usually leads to borrowing in order to cover the difference. The deficit can have both positive and negative effects, depending on how it is used and the current economic situation. This scientific paper investigates the impact of budget deficits on GDP in EU countries. The research was conducted for the period from 2000 to 2022. The aim of the study is to assess the impact of budget deficits on GDP by reviewing relevant literature and using a statistical model, specifically the GLS model in the STATA software package. In addition to budget deficits as the independent variable, the variables of inflation, healthcare, unemployment, and savings were also used. Based on the conducted research, a significant positive impact of budget deficits on GDP in EU countries was determined. Other potential factors that could have an impact were not included in the model, which may lead to bias due to omitted variables. Although the research employed advanced techniques for panel data and addressed challenges such as unbalanced panels and the presence of heteroscedasticity and autocorrelation, remaining effects may still influence the results. Future studies could include more macroeconomic variables, such as interest rates, trade balances, and the structure of public debt.